Introducing the Orthodox Churches - Gregorios, Paulos Mar. 1922-1998.; I.S.P.C.K. (Organization); Orthodox Theological Seminary. Mar Gregorios Foundation (Delhi : Jointly published for Mar Gregorios Foundation of Orthodox Theological Seminary, Kottayam and ISPCK, 1999)
Collection of articles.
"Mar Gregorios : a bibliography": (p. [75]-76).
Keywords: Orthodox Eastern Church -- History